"Secularization of Consciousness" or Alternative Opportunities? The Impact of Economic Growth on Religious Belief and Practice in 13 European Countries. Issue 2 (4th June 2013) - Hirschle, Jochen
<x xml:space="preserve">Abstract</x> This research note contributes to an evaluation of the validity of secularization theory by studying the relationship between economic modernization and patterns of religious change. Both the disenchantment narrative of Berger and Weber and the existential security perspective of Inglehart hypothesize that economic development should be accompanied by a weakening of religious values. Using macro‐level panel regressions, my analysis reveals that while economic growth is directly associated with diminishing church attendance rates, it is not directly associated with a decline in belief. The relation between economic growth and religious decline is therefore not primarily mediated by a "secularization of consciousness." Findings instead indicate that economic prosperity leads to a change in consumption patterns on the part of individuals due to increased income and availability of alternative, secular opportunities to meet needs previously fulfilled by traditional religion. A decline in religious belief may occur as a secondary consequence of this behavioral change, since diminishing worship attendance rates reduce the influence of religion on value socialization.